Problemy polskiego szkolnictwa zaboru pruskiego i rosyjskiego na kartach „Szkoły” 1868-1914 - Wnęk, Jan (Biuletyn Historii Wychowania, 2008)
The article discusses the period 1868-1914. At that time in Lvov, a pedagogical magazine entitled Szkoła (“School”) was published, in the columns of which one could find articles dealing with the problems of the Polish educational system in the Prussian and Russian partition zones. They were primarily letters and publications based on information obtained from brochures, newspapers and periodicals issued in the Grand Duchy of Poznan and the Kingdom of Poland. The news concerning Polish education published in Szkoła were non systematic and did not appear in cycles. Nevertheless, they possessed largely informative value for the readers of the periodical. They depicted the struggle to preserve the Polish language in schools, the questions connected with educating at an elementary and secondary level. Some papers provided information about schools for apprentices and schools of rural economics for girls. Galician autonomy created opportunities for freedom of expression on various topics. Owing to this, the journalists printing their articles in Szkoła openly denounced the abuses of Germans and Russians, criticised Germanization and Russification.